1983
DOI: 10.1111/j.1476-5381.1983.tb09419.x
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of inhibition of histamine release from human lung fragments by sodium cromoglycate, salbutamol and chlorpromazine

Abstract: 1 Three drugs have been tested for activity against antigen-induced histamine release from passively sensitized human lung fragments after increasing periods of pre-incubation before challenge. 2 After 30 s pre-incubation, sodium cromoglycate inhibited histamine release in the concentration range 0.2-200 iM, producing a maximum inhibition of 33.0%. As the pretreatment period was extended, tolerance developed in a dose-related manner, resulting in a 48.3 % and 82.8% loss of activity of the 200 AM dose after 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
28
2

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 31 publications
6
28
2
Order By: Relevance
“…The failure of salmeterol, salbutamol, DSCG, denbufylline and ketotifen to effectively inhibit EPO release contrasts with their effect on lung mast cells where these drugs are potent inhibitors of degranulation [23, 24]. These results highlight the differences between mast cells and eosinophils as targets of anti-asthmatic drugs and may suggest that in terms of preventing degranulation, these drugs probably act more effectively on bronchial mast cells than eosinophils.…”
Section: Discussionmentioning
confidence: 75%
“…The failure of salmeterol, salbutamol, DSCG, denbufylline and ketotifen to effectively inhibit EPO release contrasts with their effect on lung mast cells where these drugs are potent inhibitors of degranulation [23, 24]. These results highlight the differences between mast cells and eosinophils as targets of anti-asthmatic drugs and may suggest that in terms of preventing degranulation, these drugs probably act more effectively on bronchial mast cells than eosinophils.…”
Section: Discussionmentioning
confidence: 75%
“…Although it is well known that (1-adrenoceptor agonists do not inhibit mediator release from rat mast cells [16,17], (1-adrenoceptor agonists are potent inhibitors of histamine release in human lung fragments [6,7,18,19], dispersed human lung mast cells [9,20,21], human skin slices [19], dispersed human skin mast cells [4], and in in vivo studies of human skin [22][23][24], (1-adrencrgic receptor activation also inhibits antigen-induced peptidoleukotricne genera tion by human lung fragments [19] and dispersed lung mast cells [9,20,21], Ketotifen is a derivative of the tricyclic compound, benzocycloheptathiophcne, that differs markedly in its chem ical structure from any of the classic antihistamines [25,26], Ketotifen (10-200 \iM) inhibits histamine release from rat peritoneal mast cells using non-immunologic stimuli [27][28][29][30]. Ketotifen also inhibits the release of histamine and slow-reacting substance of anaphylaxis (SRS-A) leukotrienes from peripheral human leukocytes induced by both immunogenic (anti-IgE) and non-immunogenic (cal cium ionophore A23187) stimuli [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now generally accepted that mast cells from different species, and even from di verse tissues within a given animal, are functionally het erogeneous [4,5], In particular, they may vary in their re sponses to particular anti-allergic agents. It has already been demonstrated that the responsiveness of IgE-mediated histamine release to modulation by sodium cromoglycate (SCG) differs markedly between human skin and lung mast cells [4], In mast cells dispersed from human lung tissue [6][7][8][9] and adenoids [10], SCG is a weak inhib itor of histamine and prostaglandin (PG) D2 release. On the other hand, in skin mast cells SCG has no inhibitory ef fect on IgE-dependent histamine release in in vitro [4,11,12] and in vivo studies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Antigen induced weal formation in the skin is a consequence of mediator release from mast cells activated by IgE. Salbutamol is a potent inhibitor (some 102_103 more potent than cromoglycate) of IgE mediated mediator release from 'the lung in vivo (Howarth et al, 1985) and in vitro (Church & Young, 1983;Butchers et al, 1979). In the present study salbutamol showed a similar trend to adrenaline in reducing the weal response, although this did not reach significance.…”
Section: Discussionmentioning
confidence: 99%